Prevalence of Listeria Species in Ground Beef and Chicken Meat Sold in Eastern Turkey - Kalender, Hakan (Univ Agriculture, Fac Veterinary Science, 2012)
The present work aimed to investigate the prevalence of Listeria monocytogenes in ground beef and chicken samples put into the market during the period of April to September 2011 in the eastern part of Turkey. A total of 360 food samples consisting of 180 ground beef and 180 chicken meat samples were examined in terms of the presence of Listeria species. L. monocytogenes was isolated from 7.2 % ground beef samples and 17.8 % of chicken meat samples. While in 15.5% of the ground beef samples L. innocua was detected, L. welshimeri was detected in 6.1% of them. As for chicken meat samples, L. innocua was detected in 36.7% of them while L. welshimeri was detected in 5.5%, L. seeligeri was detected in 4.4% and L. murrayi was detected in 1.1% of them. Out of 45 L. monocytogenes isolates, 28 were type 1, while 17 of them were type 4. These results indicated that L. monocytogenes and other Listeria species are widely distributed in the ground beef and chicken meat samples in the eastern part of Turkey. Thus, meat products may be a potential food safety concern in Turkey. (C) 2012 PVJ. All rights reserved
Keywords: Chicken Meat; Gound Beef; L. monocytogenes